Serum Survivin and TP53 Gene Expression in Children with Acute Lym-phoblastic Leukemia - Raida S Yahya; Manal I Fouda; Hatim A El-Baz; Tamer E Mosa; Mohamed D Abd ElMaksoud (Tehran University of Medical Sciences, 2012)
Background: The aim of this study was to detect the prognostic significance of survivin level and the expression of total p53 in acute lymphoblastic leukemia (ALL) and its correlation to patients' outcome. Methods: Sixty two children newly diagnosed with acute lymphoblastic leukemia were treated with chemotherapy and followed up for 2 years or until death. Twenty apparently healthy volunteers with matched age and sex were taken as control. Survivin protein was measured by quantitative sandwich enzyme immunoassay and total human p53 was measured by Flow cytometry in peripheral blood at diagnosis and at complete remission. Results: A highly significant elevation (P<0.0001) was found in survivin protein and total p53 levels in acute lymphoblastic leukemia children patients at diagnosis compared to controls. At complete remission a significant decrease of the two indices were found in ALL patients compared to those at diagnosis (P<0.0001).  Survivin protein and total p53 was significantly higher in non-survived compared to survived group (P<0.0001 & P=0.016, respectively). A positive correlation was found between survivin level and total human p53 level in children with ALL (r=0.501 & P<0.0001). Conclusion: survivin protein is related to anti-apoptotic proteins and its high expression lead to unsuccessful treatment of ALL. Survivin and TP53 are new prognostic tools in ALL, independent of age and sex.